Changes in pollen exposure driven by intense meteorological fluctuations - Jorge Romero-Morte; Jesús Rojo; Beatriz Lara; Rosa María Rodríguez-Arias; Federico Fernández-González; Francisco Aznar; Luis Negral; Stella Moreno-Grau; José María Moreno; Rosa Pérez-Badia (Aerobiologia, 2026)

Evaluating Viral Pollution in Wastewater and Mediterranean Ecosystems - Pablo Puchades-Colera; Inés Girón-Guzmán; Enric Cuevas-Ferrando; Azahara Díaz-Reolid; Irene Falcó; Rosa Aznar; Marinella Farré; Marta Llorca; Alba Pérez-Cataluña; Gloria Sánchez (Food and Environmental Virology, 2026)

Vitamin B2 overproduction in Lactiplantibacillus plantarum: new insights in the FMN-dependent regulatory activity of the rib operon riboswitch - Angela Scauro; José Ángel Ruiz-Masó; Annel M. Hernández-Alcántara; Francisca Álvarez-Juárez; Nicola De Simone; Lidia Rodrigo; Rosa Aznar; Pasquale Russo; Giuseppe Spano; Gloria del Solar (Food Bioscience, 2026)

Probiotic Characteristics of Lactiplantibacillus plantarum CECT 9435 and Its Survival and Competitive Properties Under Simulated Conditions of the Child Gut Microbiota - Teresa Requena; M. Carmen Martínez-Cuesta; Rosa Aznar; M. Luz Mohedano; Paloma López; Patricia Ruas-Madiedo (Probiotics and Antimicrobial Proteins, 2025)
Probiotics are valuable microorganisms effective in reducing malnutrition-related infections in children. In this work, a collection of lactobacilli strains representative of traditional Andean fermented beverages was in vitro screened for their capability to survive the gastrointestinal transit, to adhere to the intestinal epithelium and to compete under simulated conditions of the child gut microbiota. The results allowed the selection of the riboflavin overproducing strain Lactiplantibacillus plantarum CECT 9435 based on its good rate of survival under in vitro gastrointestinal conditions when included in a food matrix representing the fortified food supplement Incaparina. The strain also showed good adhesion to HT29 cells producing mucus and outstanding performance in E. coli competition for the adhesion to this epithelial cell line. L. plantarum CECT 9435 gut performance was also evaluated in the child intestinal microbiota simulated in a dynamic gut model (BFBL simulator). The viability of the probiotic candidate in the gut conditions was high during the 7-day intervention period, reaching over 1 × 10 7 counts in each of the reactors simulating the three colonic regions. The transient viability of L. plantarum CECT 9435 within the child gut microbiota and its adhesion capacity to intestinal cells could facilitate the strain potential benefits as probiotic added to fortified supplementary foods destined to malnourished children.

MIRRI-ERIC's position on the recent evolution of the international code of nomenclature of prokaryotes - Rosa Aznar; Michel-Yves Mistou; Praveen Rahi; Jean-Luc Legras; Anete Boroduske; Amalia Stefaniu; Nelson Lima; Amalia D. Karagouni; Vincent Van de Perre; Ana M.P. Melo (Systematic and Applied Microbiology, 2025)

Human intestinal enteroids and predictive models validate the operational limits of sanitizers used for viral disinfection of vegetable process wash water - Ana Allende; José Antonio Férez-Rubio; Juan Antonio Tudela; Rosa Aznar; Maria Isabel Gil; Gloria Sánchez; Walter Randazzo (International Journal of Food Microbiology, 2024)

Exploring the impact of lactic acid bacteria on the biocontrol of toxigenic Fusarium spp. and their main mycotoxins - Eva M. Mateo; Andrea Tarazona; Rosa Aznar; Fernando Mateo (International Journal of Food Microbiology, 2023)

Pseudidiomarina piscicola sp. nov., isolated from cultured European seabass, Dicenthrarchus labrax - M. Carmen Macián; Teresa Lucena; David R. Arahal; María A. Ruvira; Rosa Aznar; María J. Pujalte (Archives of Microbiology, 2021)
Strain CECT 9734 T , a Gram-negative, aerobic, chemoorganotrophic bacterium, motile by polar flagella, was isolated from cultured European seabass, Dicenthrarchus labrax, in Spain. It grows from 5 to 42 ºC, 6–9 pH and 1–12% total salinity. Major cellular fatty acids are C 15:0 iso, summed feature 9 (C 17:1 iso w9c /C 16:0 10-methyl) and C 17:0 iso. The genome size is 2.5 Mbp and G + C content is 49.5 mol%. Comparative analysis of the 16S rRNA gene sequence shows that the strain is a member of Pseudidiomarina , with highest similarities with Pseudidiomarina halophila (97.0%) and Pseudidiomarina salinarum (96.9%). Phylogenomic tree based on UBCG program shows P. halophila as its closest relative. ANI and in-silico DDH with other Pseudidiomarina spp. are lower than 87 and 20%, respectively, suggesting that strain CECT 9734 T represents a new species, for which we propose the name Pseudidiomarina piscicola sp. nov. and CECT 9734 T (= LUBLD50 7a T = LMG 31044 T ) as type strain.

Methylobacterium symbioticum sp. nov., a new species isolated from spores of Glomus iranicum var. tenuihypharum - Jose Antonio Pascual; Margarita Ros; Jesus Martínez; Francisco Carmona; Antonio Bernabé; Rocío Torres; Teresa Lucena; Rosa Aznar; David R. Arahal; Felix Fernández (Current Microbiology, 2020)

Diversity and dynamics of lactic acid bacteria in Atole agrio, a traditional maize-based fermented beverage from South-Eastern Mexico, analysed by high throughput sequencing and culturing - Alba Pérez-Cataluña; Patricia Elizaquível; Purificación Carrasco; Judith Espinosa; Dolores Reyes; Carmen Wacher; Rosa Aznar (Antonie van Leeuwenhoek, 2018)

Natural enemies of the South American moth, Tuta absoluta, in Europe, North Africa and Middle East, and their potential use in pest control strategies - Lucia Zappalà; Antonio Biondi; Alberto Alma; Ibrahim J. Al-Jboory; Judit Arnò; Ahmet Bayram; Anaïs Chailleux; Ashraf El-Arnaouty; Dan Gerling; Yamina Guenaoui; Liora Shaltiel-Harpaz; Gaetano Siscaro; et al. (Journal of Pest Science, 2013)

Discrimination of Infectious Hepatitis A Viruses by Propidium Monoazide Real-Time RT-PCR - Gloria Sánchez; Patricia Elizaquível; Rosa Aznar (Food and Environmental Virology, 2012)